Comparing Generalized and Social Anxiety Disorders Between Sinistral and Dextral Children With Depression Symptoms - Tooraj Sepahvand; Jalil Moradi (Majallah-i dānishgāh-i ̒ulūm-i pizishkī-i Arāk, 2019)
Background and Aim There is a high correlation between depression and anxiety in children which are also related to laterality. This study aimed to compare generalized anxiety and social anxiety in sinistral and dextral children with depression symptoms. Methods & Materials This is a cross-sectional study with a causal-comparative design. The study population consisted of all primary students (fourth to sixth grade) of Arak Province in Iran. A convenience sampling method was used to select study samples. Prior to study, following questionnaires were completed: Children's Depression Inventory, Brief Scale of Generalized Anxiety Disorder, and Liebowitz Social Anxiety Scale for Children and Adolescents. Then, those with depression score of 19 and higher were assigned into two groups of sinistral (n=31) and dextral (n=35), and compared in terms of generalized anxiety and social anxiety. Ethical Considerations This study obtained its ethical approval form the Research Ethics Committee of Arak University of Medical Sciences (code: IR.ARAKMU.REC.1397.298). Results The results of multivariate analysis of variance showed a significant difference in two study varia-bles between groups (P=0.001). Moreover, based on the results of univariate analysis of variance, sinistral children had higher generalized anxiety compared to dextral children; however, they were not significantly different in terms of social anxiety. Conclusion Considering the higher vulnerability of depressed sinistral children to anxiety disorders, they are more likely to need specific ways of preventing and treating depression and generalized anxiety disorder.